The Problematics of Mobile Lending (Bank Keliling) Practices in Rural Areas: An Islamic Law Analysis of Riba and Gharar Elements and Their Implications for Rural Financial Behavior - Medi Romi Ardianto; Andriansyah Andriansyah; Dwi Ayu Widyaningsih; Rizky Ananda (Bulletin of Community Engagement, 2026)
This study aims to analyze the practice of mobile lending (“bank keliling”) in Banjit Subdistrict, Way Kanan Regency from the perspective of Islamic law, particularly in relation to the elements of riba (usury) and gharar (uncertainty), as well as to examine its implications for rural financial behavior. This research employs a socio-legal approach with a qualitative method through in-depth interviews, observation, and documentation involving 66 informants, including community members, lenders, religious leaders, and local authorities. The findings reveal that although the practices vary in form, they fundamentally contain elements of riba, either explicitly or disguised under terms such as “profit-sharing,” thereby violating the fiqh maxim kullu qardin jarra naf’an fahuwa riba and the principle of al-ghunmu bi al-ghurmi. Furthermore, significant elements of gharar are identified, reflected in unclear contracts, lack of transparency, and the absence of written agreements, which contradict the principle of clarity in transactions and the maxim al-‘ibrah fi al-‘uqud li al-maqasid wa al-ma’ani. The joint liability system also violates the principles of la dharar wa la dhirar and al-darar yuzal as it creates disproportionate collective harm. Empirically, these practices contribute to unhealthy financial behavior, including debt dependency, consumptive patterns, and recurring debt traps. This study concludes that mobile lending practices are not only inconsistent with Islamic law but also detrimental to rural economic stability, thus requiring comprehensive interventions through financial literacy, regulatory enforcement, and the development of inclusive sharia-based financing alternatives.